Elevated temperature differently affects growth, photosynthetic capacity, nutrient absorption and leaf ultrastructure of Abies faxoniana and Picea purpurea under intra- and interspecific competition. (17th May 2019) - Yu, Lei; Song, Mengya; Xia, Zhichao; Korpelainen, Helena; Niinemets, Ülo; Li, Chunyang
Abstract: There is a limited understanding of the impacts of global warming on intra- and interspecific plant competition. Resolving this knowledge gap is important for predicting the potential influence of global warming on forests, particularly on high-altitude trees, which are more sensitive to warming. In the present study, effects of intra- and interspecific competition on plant growth and associated physiological, structural and chemical traits were investigated in Abies faxoniana and Picea purpurea seedlings under control (ambient temperature) and elevated temperature (ET, 2 °C above ambient temperature) conditions for 2 years. We found that A. faxoniana and P. purpurea grown under intra- and interspecific competition showed significant differences in dry matter accumulation (DMA), photosynthetic capacity, nutrient absorption, non-structural carbohydrate (NSC) contents and leaf ultrastructure under ET conditions. ET increased leaf, stem and root DMA of both conifers under both competition patterns. Moreover, under ET and interspecific competition, P. purpurea had overall superior competitive capacity characterized by higher organ (leaf, stem and root) and total DMA, height growth rate, net photosynthetic rate, specific leaf area, water use efficiency (δ 13 C), leaf and root N and NSC concentrations and greater plasticity for absorption of different soil N forms. Thus, the growth of P. purpurea benefitted from the presence of A. faxoniana under ET. Our results demonstrated that ET significantly affects the asymmetric competition patterns in subalpine conifer species. Potential alteration of plant competitive interactions by global warming can influence the composition, structure and functioning of subalpine coniferous forests.